2005
DOI: 10.1007/s00441-005-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Incongruent pattern of neurokinin B expression in rat and mouse brains

Abstract: The expression patterns of Tac2 and NK3 mRNA and of pep2, the neurokinin B (NKB) precursor protein, were compared in rats and mice. Pep2 immunoreactivity was observed in fibers, terminals, and perikarya in the brains of both species, but the number of NKB-immunoreactive cells was generally smaller in mice than in the corresponding nuclei in rats. Congruent distribution patterns of Tac2 mRNA and NKB were found in many nuclei of the thalamus and hypothalamus (habenula, anterodorsal nucleus, preoptic area, arcuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…The patterns of expression of NKB and NK3R we observed in sections through the central forebrain corroborate previous studies, documenting their widespread distribution and notable regional concentrations (10). Although the functional significance of NKB/NK3R signaling in reproductive physiology is beginning to emerge (34,36,38), its relevance to other brain functions remains largely a mystery.…”
Section: Discussionsupporting
confidence: 88%
“…The patterns of expression of NKB and NK3R we observed in sections through the central forebrain corroborate previous studies, documenting their widespread distribution and notable regional concentrations (10). Although the functional significance of NKB/NK3R signaling in reproductive physiology is beginning to emerge (34,36,38), its relevance to other brain functions remains largely a mystery.…”
Section: Discussionsupporting
confidence: 88%
“…Differential expression of Tac2 (TAC3 in human and other vertebrates) in rodents has also been observed. For example, Tac2 was detected in the hippocampus and in the nucleus of the lateral olfactory tract in the rats, but not in mice (Duarte et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Loss-of-function mutations in either TAC3 or TACR3 could lead to hypogonadotrophic hypogonadism in human, indicating that the NKB/NK 3 system is indispensable for the human reproductive axis (Topaloglu et al, 2009). Neuroanatomical studies have revealed that NKB neurons are mainly located in the arcuate nucleus, sending their projections to the GnRH terminals in the median eminence where TACR3 is expressed (Abel et al, 1999;Duarte et al, 2006;Foradori et al, 2006;Goodman et al, 2007;Navarro et al, 2009;Pillon et al, 2003;Ramaswamy et al, 2010;Sandoval-Guzmán and Rance, 2004;Wakabayashi et al, 2010). These data suggest that the TAC3/TACR3 system controls reproduction by modulating GnRH secretion.…”
Section: Introductionmentioning
confidence: 85%